Farmers and the adoption of modern fertiliser: A case of irrigational farming in auyo local government area, Jigawa State, Nigeria - Abdullahi, Ahmad; Danlami, Abubakar Hamid (2020)
The study examines the determinants of fertiliser demand among irrigation farmers in Auyo Local Government Area of Jigawa State, Nigeria. Data for the study was sourced using structured questionnaire, a two-stage sampling technique was used to select the respondents. Logit regression model was estimated to analyse the factors that influence modern fertilizer adoption, the result of the estimated model shows that, marital status, farm size, farming experience, contact with extension workers, membership of association were statistically significant in determining fertiliser adoption in Auyo local government area, Jigawa State. The result further shows that the major obstacles to fertiliser adoption and use intensity include: high cost of fertilizer, lack of credit facilities, inadequate supply, untimely supply, hoarding of fertilizer by agents, hoarding of fertilizer by agents and supply of undesired type. The work recommends that, government should enhance the services of extension workers, offer micro finance services, provide credit facilities, skills and training programmes on some off – farm jobs for farmers in the study area.